Change in Security Architecture of Central and Eastern Europe in the Context of the Situation in Ukraine - Polcikiewicz, Zdzisław (Historia i Polityka, 2019)
The aggressive, imperialistic policy of Russia – expressed inter alia in the armed attack on Georgia in 2008 and the conflict with Ukraine that has lasted since 2014 – made the NATO countries aware of the existence of a real threat from the Kremlin. States bordering the Russian Federation must be especially aware that in the event of a possible armed conflict between the North Atlantic Treaty Organization and the latter country, they will be the first territories falling victim to a possible Russian attack. Faced with such risk, these countries strive for evening up of the level of military security for all members of the organization. A significant change in security architecture of the Central and Eastern Europe took place in 2017 as a result of practical implementation of two major initiatives increasing the presence of allied troops in the region: the European Reassurance Initiative (ERI) and the Enhanced Forward Presence (EFP). The aim of the present study is to introduce the basic goals and principles of the two above initiatives, as well as the activities undertaken by NATO and the USA in order to fulfill their commitments related thereto. Such activities are a manifestation of NATO’s solidarity, unity and strength, and mark the return of this organization to its original role – which is the collective defense of all member states.